Moisture content test of effervescent denture cleaner tablets made from 6.5% cocoa fruit peel (Theobroma cacao L.) : Uji kadar air pembersih gigi tiruan tablet effervescent kulit buah kakao (Theobroma cacao L.) konsentrasi 6,5% - Utama, Mohammad Dharma; Biba, Andi Tenri; Amiruddin, Maqfirah; Chotimah, Chusnul; Permita, Trias Anugerah (Makassar Dental Journal, 2025)
Effervescent tablets are a type of pharmaceutical formulation; they are a mixture of acids and bases that release carbon di-oxide and produce foam when dissolved in water. This article discusses the water content of effervescent tablets used as den-ture cleansers made from 6.5% cocoa bean shell extract (Theobroma cacao L.). A true experimental study was conducted using 16 effervescent tablets and a moisture analyser. The comparison test results showed a p-value of 0.000 (<0.05). This in-dicates that there is a significant difference in the water content of 6.5% CBS effervescent tablets and alkaline peroxide ef-fervescent tablets. It is concluded that there is a significant difference between the water content of CBS effervescent ta-blets and alkaline peroxide effervescent tablets, but both meet the requirements for good water content (≤ 10%).